Uniform and perfectly linear current–voltage characteristics of nitrogen-doped armchair graphene nanoribbons for nanowires. Issue 1 (5th December 2016) - Liu, Lingling; Li, Xiao-Fei; Yan, Qing; Li, Qin-Kun; Zhang, Xiang-Hua; Deng, Mingsen; Qiu, Qi; Luo, Yi
Abstract : Edge nitrogen-doping induces uniform and perfectly linear I – V characteristics in AGNRs for nanowire applications in molectronics. Abstract : Metallic nanowires with desired properties for molecular integrated circuits (MICs) are especially significant in molectronics, but preparing such wires at a molecular level still remains challenging. Here, we propose, from first principles calculations, experimentally realizable edge-nitrogen-doped graphene nanoribbons (N-GNRs) as promising candidates for nanowires. Our results show that edge N-doping has distinct effects on the electronic structures and transport properties of the armchair GNRs and zigzag GNRs (AGNRs, ZGNRs), due to the formation of pyridazine and pyrazole rings at the edges. The pyridazine rings raise the Fermi level and introduce delocalized energy bands near the Fermi level, resulting in a highly enhanced conductance in N-AGNRs at the stable nonmagnetic ground state. Especially for the family of AGNRs with widths of n = 3 p + 2, their semiconducting characteristics are transformed to metallic characteristics via N-doping, and they exhibit perfectly linear current–voltage ( I – V ) behaviors. Such uniform and excellent features indicate bright application prospects of the N-AGNRs as nanowires and electrodes in molectronics.